How the General Public and Local Officials Prefer to Learn about Agricultural Water Use in Florida - Courtney T. Owens; Alexa J. Lamm; Ricky W. Telg (EDIS, 2016)
Water is a precious resource that is invaluable to the state of Florida. The amount of water being used daily in the state is estimated at 14.3 million gallons. Part of a series dedicated to describing the preferred ways of learning about agricultural water use in Florida, this study can be used to assist Extension educators and the agricultural industry at large in the development of strategies meant to inform people about the realities of water use. This 4-page fact sheet helps Extension educators understand preferred learning mediums so they can provide useful information about agricultural water use. Written by Courtney T. Owens, Alexa J. Lamm, and Ricky W. Telg, and published by the Agricultural Education and Communication Department, April 2016.